Mast Cells and Basophils in Major Viral Diseases: What Are the Correlations with SARS-CoV-2, Influenza A Viruses, HIV, and Dengue? - Luca Gammeri; Serena Sanfilippo; Clara Alessandrello; Sebastiano Gangemi; Paola Lucia Minciullo (Cells)
The SARS-CoV-2 pandemic has significantly impacted global health and has led the population and the scientific community to live in fear of a future pandemic. Based on viral infectious diseases, innate immunity cells such as mast cells and basophils play a fundamental role in the pathogenesis of viral diseases. Understanding these mechanisms could be essential to better study practical therapeutic approaches not only to COVID-19 but also to other viral infections widely spread worldwide, such as influenza A, HIV, and dengue. In this literature review, we want to study these concepts. Mast cells and basophils intervene as a bridge between innate and acquired immunity and seem to have a role in the damage mechanisms during infection and in the stimulation of humoral and cellular immunity. In some cases, these cells can act as reservoirs and favor the replication and spread of the virus in the body. Understanding these mechanisms can be useful not only in therapeutic but also in diagnostic and prognostic perspectives. The prospects of applying artificial intelligence and machine learning algorithms for the creation of very accurate diagnostic/prognostic tools are interesting.